UJI EFEK EKSTRAK ETANOL DAUN KUCING-KUCINGAN (Acalypha Indica L.) TERHADAP KADAR GULA DARAH TIKUS PUTIH JANTAN GALUR WISTAR (Rattus novergicus) - Kawatu, Cheryl; Bodhi, Widdhi; Mongi, Jeane (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT The cooperleaf herb (Acalypha indica L.) is a plant which is used as a traditional medicine. The cooperleaf herb leave is a part of the plant to use for decreasing the blood sugar level. The aimed of this research is to know the giving effect of the cooperleaf herb leave ethanol extract to the blood sugar level of strain wistar white male mice which is inducted by sucrose. Fifteen strain wistar white male mice are divided into five treatment groups namely negative control group, positive control group, the group of the cooperleaf herb leave extract with doses 3,15 g extract/ kg body weight, 6,3 g extract/ kg body weight, and 12,6 g extract/ kg body weight. The data obtained from the examinationÂ by sucrose and at 15, 30, 60, 120 minutes after gave treatment. The data are analyzed by using One Way ANOVA and to be continued with LSD test for seeing the differentiation between the treatments. The result of this research show the cooperleaf herb leave ethanol extract with with doses 3,15 g extract/ kg body weight, 6,3 g extract/ kg body weight, and 12,6 g extract/ kg body weight have the effect to decrease the blood sugar level of strain wistar white male mice.